2014
DOI: 10.4103/0971-3026.137037
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in evaluation of peripheral nerves

Abstract: Ultrasonography (USG) is an excellent cost-effective modality in imaging of peripheral nerves. With the newer high-frequency probes with different footprints which allow high-resolution imaging at relatively superficial location, USG can detect and evaluate traumatic, inflammatory, infective, neoplastic, and compressive pathologies of the peripheral nerves. This article describes the technique for evaluation of nerves by USG as well as the USG appearances of normal and diseased peripheral nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
72
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 14 publications
2
72
0
3
Order By: Relevance
“…More recently, high‐resolution ultrasound (HRU) has been used to evaluate peripheral nerves, particularly focal nerve entrapments and, increasingly, for evaluation of peripheral neuropathies . HRU is a low‐cost, quick, noninvasive imaging tool that provides morphological information about peripheral nerves and their surrounding tissues that is complementary to EDx studies, enabling integration of structural and physiologic information . Further, HRU images depict nerves with high image quality, which enables clinicians to examine long segments of peripheral nerves along their anatomical course while allowing dynamic imaging .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, high‐resolution ultrasound (HRU) has been used to evaluate peripheral nerves, particularly focal nerve entrapments and, increasingly, for evaluation of peripheral neuropathies . HRU is a low‐cost, quick, noninvasive imaging tool that provides morphological information about peripheral nerves and their surrounding tissues that is complementary to EDx studies, enabling integration of structural and physiologic information . Further, HRU images depict nerves with high image quality, which enables clinicians to examine long segments of peripheral nerves along their anatomical course while allowing dynamic imaging .…”
mentioning
confidence: 99%
“…2 HRU is a low-cost, quick, noninvasive imaging tool that provides morphological information about peripheral nerves and their surrounding tissues that is comple-mentary to EDx studies, enabling integration of structural and physiologic information. [3][4][5] Further, HRU images depict nerves with high image quality, which enables clinicians to examine long segments of peripheral nerves along their anatomical course while allowing dynamic imaging. 6 Recent work has demonstrated that peripheral nerve ultrasonography is reliable and reproducible.…”
mentioning
confidence: 99%
“…The US findings associated with the CTS have been described in adults and they consist of the increased size of the median nerve proximal to the flexors retinaculum, sudden change in size at the level of the tunnel outlet, decreased echogenicity, decreased mobility and increase of the Doppler signal [27,28]. According to the knowledge of the authors no studies regarding the US evaluation of the median nerve in MPS II patients have been published.…”
Section: Discussionmentioning
confidence: 90%
“…Nerves in leprosy are enlarged and exhibit structural abnormalities such as fusiform swelling, loss of fascicles, oedema and increased vascularity on sonography 10. Ultrasound imaging in a nerve abscess shows diffusely thickened nerve housing a hypoechoic cystic lesion with internal debris,2 whereas peripheral nerve sheath tumours appear as well-defined ovoid homogenous hypoechoic lesions with nerve entering and exiting from them 11. MRI may show diffuse oedema and swelling of the involved nerve due to neuritis.…”
Section: Discussionmentioning
confidence: 99%